Lipschitz stability for the finite dimensional fractional Calderón problem with finite cauchy data - Rüland, Angkana; Sincich, Eva (Arxiv, 2018)
In this note we discuss the conditional stability issue for the finite dimensional Calder\'on problem for the fractional Schrödinger equation with a finite number of measurements. More precisely, we assume that the unknown potential